Rapid risk assessment during the early weeks of the 2015‐2016 influenza season in Ukraine. Issue 2 (15th January 2018) - Newitt, Sophie; Mironenko, Alla; Holubka, Olha; Zaika, Oleksandr; Gubar, Olga; Jalava, Katri; Brown, Caroline; Demchyshyna, Iryna; Dykhanovska, Tetiana
Abstract : Background: Several eastern European countries reported a severe influenza season to the World Health Organization (WHO) during late 2015. A country‐specific rapid risk assessment for Ukraine was conducted to assess the season's severity and inform public health action. Methods: The exposure and hazard were assessed using acute respiratory infection (ARI), severe acute respiratory infection (SARI), laboratory surveillance, virological and vaccine data from weeks 40/2015 to 7/2016 with comparison to 4 previous seasons to describe the influenza season start (5‐week consecutive increase in ARI or SARI), predominant virus types, geographical spread and affected age groups. Results: The exposure was characterised by an earlier and steeper increase in SARI (week 1/2016) and ARI (week 2/2016) compared to the previous 4 seasons. Transmission was across Ukraine with an increase in ARI and SARI cases aged 30‐64 years compared to 2014/15. Laboratory‐confirmed deaths increased from 11 in 2014/2015 to 342 in 2015/2016; the majority were 30‐64 years old and unvaccinated; and 63.5% had underlying conditions. Total population vaccination coverage was 0.3%. The hazard assessment found influenza virus A(H1N1)pdm09 accounted for >95% of viruses detected. Ukrainian virus strains (n = 62) were antigenically similar to vaccine strains and susceptible to neuraminidase inhibitors. Conclusions: The first weeks of the 2015/16 influenza season were more severe than previous seasons, with an earlier and steeper increase in severe cases and deaths, particularly in younger adults. Influenza A(H1N1)pdm09 was the predominant strain and was closely related to the seasonal vaccine strain with no evidence of resistance to antiviral drugs.